Analisis Kebutuhan Pengembangan Kemampuan Speaking dan Listening Personel Pemandu Lalu Lintas Penerbangan Sesuai Dengan Ketentuan ICAO - Imam Sonhaji; Surya Tri Saputra; Emilia Rahajeng Larasati (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2023)
ICAO stipulates that English is the main language in communication between pilots and Air Traffic Controllers (ATC), so ATCs are required to have ICAO English Proficiency (IELP) skills at least level 4 (operational level) and are checked every three years, but found on during the checking test by the rater, several ATCs in Indonesia did not reach level 4 (operational level). This study explores ATC's perceptions of the IELP requirements and the accompanying matters. This study used a survey research method by distributing questionnaires, observing, and interviewing IELP Rater personnel. The result is that phraseology and simple language have different functions in the context of their usage situations. Simple English is used in emergencies or abnormal conditions. The most difficult testing component is grammar for Indonesian ATC, the supporting skills needed by ATC are writing and reading, the testing model face to face is still the priority, and the qualifications of Interlocutors, Raters are expected to be native speakers. ATC feels that the IELP test is difficult and requires pre-test preparation. ATC work uses English skills as basic capital, such as coordinating with pilots or adjacent units. The development of the IELP test model is more emphasized in the IELP pre-test training